(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today world is facing waste water pollution due to sewage water, industrial waste thermal waste water etc. and also low water level of earthen water inside the earth. This study show that how the waste water (polluted water) are clean and absorb by the earth through an artificial ponds, lakes or river after the waste water is treated in dome type structure given in waste water treatment plants in this study. This study also show that how we generate the biogas( combination of gases like methane, butane, propane or other hydro carbon gases) through waste water treatment plant and this gases is burn in thermal power plants, buses ,small trucks( auto vehicle) to create energy and utilize it in to make electricity and movement of the vehicles.